2013
DOI: 10.1007/978-3-642-40084-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Coding for Streaming Authentication and Interactive Communication

Abstract: Abstract. Error correction and message authentication are well studied in the literature, and various efficient solutions have been suggested and analyzed. This is however not the case for data streams in which the message is very long, possibly infinite, and not known in advance to the sender. Trivial solutions for error-correcting and authenticating data streams either suffer from a long delay at the receiver's end or cannot perform well when the communication channel is noisy.In this work we suggest a const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 23 publications
0
62
0
Order By: Relevance
“…Later, Braverman and Rao [5] showed that an adversarial error rate of up to ǫ < 1/4 could be tolerated with a constant overhead α = Θ (1). Lastly, [4,6,7,10,11] determined the full error rate region in which a non-zero communication rate is possible in a variety of settings. While the initial coding schemes were not computationally efficient, because they relied on powerful but hard to construct tree codes, later results [1,2,9,10] provided polynomial time schemes using randomization.…”
Section: Prior Workmentioning
confidence: 99%
“…Later, Braverman and Rao [5] showed that an adversarial error rate of up to ǫ < 1/4 could be tolerated with a constant overhead α = Θ (1). Lastly, [4,6,7,10,11] determined the full error rate region in which a non-zero communication rate is possible in a variety of settings. While the initial coding schemes were not computationally efficient, because they relied on powerful but hard to construct tree codes, later results [1,2,9,10] provided polynomial time schemes using randomization.…”
Section: Prior Workmentioning
confidence: 99%
“…Other computationally efficient encoding schemes have been developed [BK12, BN13, BKN14, GMS11, GMS14, GH14]. The communication rates under various scenarios have also been studied [BE17,GHS14,EGH15,FGOS15]. However, the rates do not approach the capacity expected of the noise rate.…”
Section: Classical Results With Efficient Encoding and Decodingmentioning
confidence: 99%
“…Later, Braverman and Rao [6] improved the tolerated error rate to < 1/4. Franklin et al [10] showed that constant rate cannot be achieved if the error rate is above 1 2 . As mentioned in [15], the initial interactive coding schemes are not computationally efficient because the involved tree codes are complicated to construct.…”
Section: Related Workmentioning
confidence: 99%